REKONSTRUKSI PEMAHAMAN KONSEP I’JAZ AL-QUR’AN PERSPEKTIF GUS BAHA’ - Nur sholihah Zahro’ul Isti’anah; Zaenatul Hakamah (Institut Agama Islam Negeri (IAIN) Keiri, 2019)
Generally the miracles of the Prophets are understood to be something sensory, just as the Prophet Musa parted the sea with his staff; Prophet Ibrahim did not feel burning on heat in the embers; Prophet Isa healed the sick and raised the dead. However, according to KH. Bahauddin Nur Salim (Gus Baha’), this understanding needs to be improved, as he conveyed in the Darusan Menara Timur study on May 29, 2019 and published on Youtube. This article will outline the study with content analysis methods using reconstruction theory. From the results of the analysis, it was concluded that from the perspective of Gus Baha’, understanding i’ja>z as something sensory is wrong, especially understanding the miracles of the Qur’an that can be witnessed not by the five senses, but by reasoning and the eyes of the heart (bas i>rah). Understanding miracles as something unusual and unmatched also needs to be clarified. Because, God’s creations are considered ordinary as mentioned in the QS. Al-Baqarah verse 26- mosquitoes are also Allah’s qudrats that cannot be imitated by humans. Its miracle lies in the ability of reason to understand its awesomeness. The mistake of understanding the concept of i’ja >z can have an impact on the value of faith, because the faith that grows from the ability to witness miracles through prayer will be of higher quality and more lasting than the faith that grows from the ability to witness in the senses.